Homogenization of Elastic Properties of Short Fiber Reinforced Composites Based on Discrete Microstructure Data. Issue 1 (29th November 2013) - Müller, Viktor; Böhlke, Thomas; Dillenberger, Felix; Kolling, Stefan
Abstract: Since the microstructure of short fiber reinforced composites is inhomogeneous, the application of micromechanical models is useful, that take into account their characteristics like the fiber orientation and the aspect ratio of fibers. Two different methods are considered in this work: A two‐step approach is utilized to get approximately the upper and lower bounds of the elastic properties. Furthermore, an approximation for the elastic properties is calculated by the self‐consistence method. Both methods use discretely microstructural information including the length, the diameter and the orientation of each single fiber. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)